De parientes a vecinos : evolución de las redes de parentesco y la solidaridad familiar en un espacio urbano en transformación: El Ensanche Sur de Madrid (1860-1905) - Fernando Vicente Albarrán (Nuevo mundo - Mundos Nuevos, 2008)
From mid century XIX, the Spanish capital’s accelerated population increase originated deep changes in its morphology and its structure like city, as well as in the social realities that welcomed. The guidelines of behaviour between the social individuals, families and groups experienced great transformations at a time of great changes and rooted traditions, to the time that the familiar strategies varied based on the time and of the social class. In order to analyze social behaviours in constant evolution, the information provided by the municipal registers of 1860, 1878 and 1905 of South Extension of Madrid will be analyzed. Madrilenian Extension, and in individual their South zone, is a privileged scope of study, because it meant an ambitious project that opened to Madrid to the outside, and a new space where a population arrived that left its old habits of life in the heat of to integrate in a city transformation.